Feeding Behaviors in Infants With Prenatal Opioid Exposure: An Integrative Review. (October 2020) - McGlothen-Bell, Kelly; Cleveland, Lisa; Recto, Pamela; Brownell, Elizabeth; McGrath, Jacqueline
Abstract : Background: Oral feeding is one of the most complex maturational skills of infancy. Difficulties with feeding require specialized attention, and if not well managed, may prolong the newborn's hospital length of stay. This is particularly true for prenatally opioid exposed (POE) infants. A paucity of literature exists characterizing feeding behaviors of POE infants, yet feeding problems are common. Purpose: The purpose of this integrative review was to synthesize and critically analyze the evidence that characterizes feeding behaviors in full-term, POE infants. Methods/Search Strategy: The electronic databases of CINAHL, PubMed, Scopus, and PsycINFO were used. Inclusion criteria were studies in English, conducted from 1970 to 2019, with participant samples consisting of infants with prenatal opioid exposure, born full-term, and between 38 and 40 weeks of gestation. Based on the inclusion criteria, our search yielded 557 articles. After further screening, only 4 studies met our full inclusion/exclusion criteria. These studies were analyzed for evidence of infant feeding behaviors, including characterization of problematic feeding behavior for POE infants. Findings/Results: Our findings revealed inconsistencies in characterization of feeding behaviors among POE infants. A synthesis of the most common evidence-based behaviors was constructed. Infant feeding behaviors were identified and grouped into 2 major behavior domains: (1) typical feeding behavior and (2) problematic feeding behavior. Implications for Practice and Research: Feeding behaviors related to sucking and behavioral states may be different in POE infants. Further examination of effective assessment methods and the categorization of infant feeding behaviors are warranted for use in the development of evidence-based, targeted intervention.